Comparative study of palatal rugae pattern in class II div 1 and class I individuals - Gandikota, Chandrasekhar (Medknow Publications & Media Pvt Ltd, 2012)
AIMS: To determine if the palatal rugae have a characteristic pattern in untreated class II div 1 malocclusions compared to normal class I occlusions, and to provide a valuable insight whether palatal rugae can be taken up as additional criteria for classifying malocclusions. MATERIALS AND METHODS: The study was conducted on initial maxillary dental casts of 24 individuals with untreated class II div 1 malocclusion with an overjet of minimum of 5mm, of whom 12 were females and 12 were males, with age ranging from 16 to 24 years and compared with Class I patients casts. RESULTS: There was no statistically significant difference in the mean intermolar widths of the two groups. The first, second and third palatal rugae were shorter in class II div 1 patients than in class I patients which was statistically significant. All the patients with Angle's class I occlusion had good pattern of palatal rugae falling in the score range of 1–3, whereas 22% of the patients with class II div 1 had poor pattern of palatal rugae, with score 4 and 2 patients exhibiting a score of 4 and 5, respectively, but this was not statistically significant. CONCLUSION: There was a significant constriction of the palatal rugae in class II div 1 individuals as compared to class I individuals, though they were matched for the same intermolar widths. There was a distinct pattern of palatal rugae between the two groups.